As beautiful inside, as it is outside: On the connection between beauty and morality in the Old English corpus - Minaya Gómez, Francisco Javier (Complutense Journal of English Studies, 2019)
This paper aims to look into the link between the experience of beauty at a sensory level and its connection with more cognitive considerations in Anglo-Saxon England. To do so, I have carried out a complete analysis of the usage of the Old English adjective fæger, one of the main descriptors of beauty in the linguistic variety. Using the Dictionary of Old English Corpus, I have created a concordance and a database containing all its attested forms, which I have analysed following diverse sociolinguistic criteria. This analysis has proven that the evaluation of beauty as rendered by Old English fæger had a strong cognitive component, mainly related to the moral and spiritual virtues of the aesthetic object and often visually represented by an abundance of light. According to this analysis, the experience of beauty in Anglo-Saxon England constitutes a rare experience that in most cases, goes beyond the sensory and the purely physical. El propósito de este artículo es investigar la conexión entre la experiencia de la belleza a un nivel sensorial y su conexión con aspectos más cognitivos en la Inglaterra anglosajona. Para ello, he llevado a cabo un análisis completo del uso del adjetivo fægerperteneciente al inglés antiguo, uno de los principales descriptores de belleza en la variedad lingüística. Usando el Dictionary of Old English Corpus, he creado una concordancia y una base de datos con sus distintas atestaciones, las cuales he analizado siguiendo diversos criterios sociolingüísticos. Este análisis ha demostrado que la evaluación de la belleza tal y como es descrita por fæger tenía un fuerte componente cognitivo, principalmente relacionado con las virtudes morales y espirituales del objeto que a menudo son representadas visualmente con una abundancia de luz. De acuerdo con este análisis, la experiencia de la belleza en la Inglaterra anglosajona constituía una experiencia poco frecuente que en la mayoría de casos traspasaba las barreras de lo sensorial y lo puramente físico.